2011
DOI: 10.1590/s1519-69842011000300017
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecomorphology of Siluriformes (Pisces, Osteichthyes) from a tropical stream

Abstract: The present study analysed the relationship between morphology and trophic structure of Siluriformes (Pisces, Osteichthyes) from the Caracu Stream (22º 45' S and 53º 15' W), a tributary of the Paraná River (Brazil). Sampling was carried out at three sites using electrofishing, and two species of Loricariidae and four of Heptapteridae were obtained. A cluster analysis revealed the presence of three trophic guilds (detritivores, insectivores and omnivores). Principal components analysis demonstrated the segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…The main goal of ecomorphology is to understand the response of organisms to environmental challenges, by comparing patterns of variations in morphological and ecological characters (Motta et al, 1995). Ecomorphological analysis can be used to describe patterns along niche dimensions, since the body shape provides relevant information about the use of resources by organisms (Bourke et al, 1997;Fugi et al, 2001;Pagotto et al, 2009Pagotto et al, , 2011Oliveira et al, 2010;Sampaio et al, 2013). For example: the depressed and elongated body of armored catfishes (Siluriformes: Loricariidae) permits a more efficient occupation of the bottom in lotic habitats, since this adaptation compensates the difficulties caused by the current, eliminating the effect of drag forces that tend to elevate their body .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of ecomorphology is to understand the response of organisms to environmental challenges, by comparing patterns of variations in morphological and ecological characters (Motta et al, 1995). Ecomorphological analysis can be used to describe patterns along niche dimensions, since the body shape provides relevant information about the use of resources by organisms (Bourke et al, 1997;Fugi et al, 2001;Pagotto et al, 2009Pagotto et al, , 2011Oliveira et al, 2010;Sampaio et al, 2013). For example: the depressed and elongated body of armored catfishes (Siluriformes: Loricariidae) permits a more efficient occupation of the bottom in lotic habitats, since this adaptation compensates the difficulties caused by the current, eliminating the effect of drag forces that tend to elevate their body .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, morphological patterns in assemblages tend to characterize species groups that explore the same ecological resource -e.g., species in the same trophic guild may present a higher morphological similarity, independently of their phylogenetic distance , since the exploitation of specific food items in an ecosystem can be facilitated by a specific design (Wootton, 1992;Norton & Brainerd, 1993;Gerking, 1994;Norton, 1995;Winemiller, et al, 1995;Montaña & Winemiller, 2009;Sampaio et al, 2013). For this reason, some authors attribute to the morphology the ability to predict the ecological niche -i.e., how the body shape selects the ecological space in a given habitat, and consider that ecomorphology can be used as a tool in analysis of assemblage structure (Winemiller, 1991;Casatti & Castro, 2006;Oliveira et al, 2010;Pagotto et al, 2011). On the other hand, since fish diets are diverse (using all available food resources in the environment), it is reasonable to question whether there are general patterns of use of prey and whether these patterns are related to the diversity of feeding mechanisms (Wainwright, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…If such associations gain phylogenetic support, i.e., if phylogenetically unrelated species exhibit convergence and related species exhibit morphological divergences, the hypothesis gains considerable power of inference (Wainwright & Reilly, 1994). Several studies have shown consistent relationships between morphology and feeding habits (Pouilly et al, 2003;Oliveira et al, 2010;Pagotto et al, 2011;Mise et al, 2013), demonstrating different predictive models of community structure (Casatti & Castro, 2006;Oliveira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aware of the limitations of this approach, but at the same time, considering it an important alternative in the attempt to express the ecology of the species, in the present study ecomorphological indexes were calculated combining the morphological measures and areas: compression index; depression index; relative length, height and width of the caudal peduncle; relative length, height and width of the head; vertical eye position, relative area of the eye and fins (dorsal, anal, caudal, pectoral and pelvic). The indexes were selected according to Gatz (1979), Winemiller (1991), Mazzoni et al (2010), Oliveira et al (2010), and Pagotto et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the difficulties aforementioned, recent studies have shown that there is a significant relationship between morphological variations and ecological aspects, such as feeding and habitat occupation (e.g. Teixeira & Bennemann, 2007;Oliveira et al, 2010;Pagotto et al, 2011;Santos et al, 2011). From these studies, the interspecific morphological variation seems to have an important role in the ecological aspects, favoring the ecological diversification of the species, providing niche differentiation and, consequently, the coexistence of the species.…”
mentioning
confidence: 99%